Studies on Co2+, Ni2+ and Cu2+ Complexes with Schiff Bases Derived from Benzil Monohydrazone - Kumar Singh, Arun; Sharma, U.N. (Asian Journal of Chemistry, 2010)
The synthesis of Co2+, Ni2+ and Cu2+ complexes of Schiff bases derived from the condensation of ethanolic solution of benzil monophenyl hydrazone with aniline and substituted anilines (in presence of H2O, α,β,γ picoline and pyridine). The complexes are characterized by elemental analyses, magnetic, IR, electronic, mass spectra and thermal studies. The schiff base behaves as a tridentate ligand. Spectral studies shows the dimeric nature of complexes.